Improving Students Listening Skill by Using Audio Visual Media - Mei Hardiah (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2019)
Teaching Listening skills to the students who learn English as a foreign language is a challenge for the teacher . This classroom action research (CAR) designed to improve the listening ability of students by using audio-visual media. The subject of this research are students of English, University of Bengkulu Diploma Program who take the course Listening For Lecture . This study was conducted in two cycles of progress namely; planning, observation, action and reflection. Moreover, collaborative learning methods are also applied to stimulate student activeness in the classroom. The results showed that the use of audio visual media is able to improve the results of listening course. In addition, the students also Become more motivated and enthusiastic during the lecture which can be seen in the group discussion stage that implement colaborative learning. Generally it can be concluded that audio visual media can improve the focus and concentration of students in listening courses. In addition to the use of audio visual media, the selection of the topic material also influence the results of students listening comprehension.